Global Risks, Vulnerabilities, and Policy Challenges Facing Low-Income Countries. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
The rapid recovery in many low-income countries (LICs) following the global crisis has been sustained in 2012. Softening commodity prices have led to moderating inflation pressures in most LICs. However, progress in rebuilding policy buffers has halted over the past two years, despite continued strong growth in LICs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet